Current issues in research communications: open access and the research economy - 1st report to JISC, March 2010 - Hubbard, Bill (Centre for Research Communications, 2010)
This report identifies some significant issues in the practice of research communication, with special reference to methods of promoting open access to research outputs. In particular it addresses the following questions: • Can open access offer financial benefit to HE institutions and to the wider economy? • How can the costs of open access publication be met by research funders and/or institutions? • What is the role of an institutional repository in the management of research across an institution?